The long run stability of money in the proposed East African Monetary Union - Simplice Asongu; Oludele E. Folarin; Nicholas Biekpe (African Governance and Development Institute (AGDI), 2020)
This study investigates the stability of money in the proposed East African Monetary Union (EAMU). The study uses annual data for the period 1981 to 2015 from five countries making up the East African Community (EAC). A standard money demand function is designed and estimated using a bounds testing approach to co-integration and error-correction modeling. The findings show divergence across countries. This divergence is articulated in terms of differences in CUSUM (cumulative sum) and CUSUMSQ (CUSUM squared) tests, short run and long term determinants and error correction in event of a shock. Specifically, the results show that the demand for money is stable in the cases of Burundi, Rwanda and Tanzania based on the CUSUM and CUSUMSQ tests, while for the remaining countries (Kenya and Uganda) only partial stability is apparent. In event of a shock, Kenya will restore its long run equilibrium fastest, followed by Tanzania and Burundi.
Keywords: E41; C22; O55; 330; Stable; demand for money; bounds test